2011
DOI: 10.1530/rep-10-0387
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of spontaneous preterm birth based on the genetic ablation of biglycan and decorin

Abstract: Preterm premature rupture of membranes is responsible for one third of preterm births. Ehlers-Danlos syndrome (EDS) is associated with preterm premature rupture of membranes in humans. Notably, an EDS variant is caused by a genetic mutation resulting in abnormal secretion of biglycan and decorin, two small leucine-rich proteoglycans highly expressed in reproductive tissues. Because biglycan/decorin null mutant (Bgn−/−Dcn−/−) mice demonstrate phenotypic changes similar to EDS, we utilized this model to test whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 68 publications
(92 reference statements)
5
42
2
Order By: Relevance
“…Finally, data showed that births in Def mice were more likely to occur preterm (ϽE18) compared with Suff mice. The percentage of births less than E18 in vitamin D-deficient mothers was similar to that reported for biglycan and decorin knockout mouse models of spontaneous preterm birth (52). Epidemiological studies have yet to demonstrate a clear association between vitamin D deficiency and spontaneous pre- term birth in humans (28), and at present there are no data for iatrogenic (clinically indicated) preterm births secondary to disorders such as preeclampsia in relation to maternal vitamin D status.…”
supporting
confidence: 76%
“…Finally, data showed that births in Def mice were more likely to occur preterm (ϽE18) compared with Suff mice. The percentage of births less than E18 in vitamin D-deficient mothers was similar to that reported for biglycan and decorin knockout mouse models of spontaneous preterm birth (52). Epidemiological studies have yet to demonstrate a clear association between vitamin D deficiency and spontaneous pre- term birth in humans (28), and at present there are no data for iatrogenic (clinically indicated) preterm births secondary to disorders such as preeclampsia in relation to maternal vitamin D status.…”
supporting
confidence: 76%
“…Examples include skin, bone, muscle, kidney and cornea (Ameye and Young, 2002; Corsi et al, 2002; Zhang et al, 2009) as well as our observations in the placenta (Calmus et al, 2011). Furthermore, fibromodulin and lumican, another pair of SLRPs, compensate for each other in tendon (Svensson et al, 1999).…”
Section: Discussionmentioning
confidence: 58%
“…Previously, we demonstrated that Bgn −/− ;Dcn −/− mice have an increased incidence of preterm birth (Calmus et al, 2011). MMPs and their inhibitors, TIMPs, as well as their targets, collagens, play a key role in the control of turnover of extracellular matrix in fetal membranes at term rupture as well as at preterm premature rupture of fetal membranes (Parry and Strauss, 1998).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The observation that low gestational 25OHD also causes prematurity in rodent models is supported by a study from Liu et al which focused on prenatal morphology of offspring from 25OHD deficient mice. They showed that maternal gestational 25OHD deficiency leads to a higher rate of premature births, that is even comparable to established knockout models of prematurity [49,52].…”
Section: Discussionmentioning
confidence: 70%